2009
DOI: 10.1002/hlca.200900235
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Studies of Different Quinolinone Derivatives as Donors in Fluorescence‐Resonance‐Energy Transfer (FRET) – Systems in Combination with a (Bathophenanthroline)ruthenium(II) Complex as Acceptor

Abstract: We describe the preparation as well as a detailed photophysical study of Fmoc-amino acid building blocks carrying different carbostyril (¼ quinolin-2(1H)-one) heterocycles as donors in a FRET (fluorescence-resonance-energy transfer) system in combination with a [Ru II (bathophenanthroline)] complex (bathophenanthroline ¼ 4,7-diphenyl-1,10-phenanthroline). The efforts resulted in a clear preference for building block 16 due to its ease of synthesis (Scheme 2), its chemical robustness, and the FRET efficiency wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…shown in Ref. ) suitable to outclass similar and wide‐used coumarin derivatives . In a recent project, we reported about the interesting fluorescence properties of 3‐aryl‐4‐cyano‐6‐methoxycarbostyrils with excitation wavelengths above 400 nm and emission wavelengths above 500 nm, with quantum yields of about Φ = 0.23.…”
Section: Introductionmentioning
confidence: 99%
“…shown in Ref. ) suitable to outclass similar and wide‐used coumarin derivatives . In a recent project, we reported about the interesting fluorescence properties of 3‐aryl‐4‐cyano‐6‐methoxycarbostyrils with excitation wavelengths above 400 nm and emission wavelengths above 500 nm, with quantum yields of about Φ = 0.23.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these 6,7‐4 push–pull substituted quinolone dyes show high thermal and photochemical stability and no oxygen quenching different from many other fluorophores. Recently, another work group incorporated our 4‐trifluoromethyl and 4‐cyanocarbostyrils into peptides and got an efficient fluorescence‐resonance‐energy transfer (FRET) system .…”
Section: Introductionmentioning
confidence: 99%
“…In a comparative study of different carbostyril derivatives, the chromophore in 1 showed the highest quantum efficiency Φ F . Therefore, 1 yielded an improved FRET performance in combination with the Ru (II) bathophenanthroline complex as acceptor due to a larger R 0 . In addition to that, 1 was accessible in just five synthetic steps in a straightforward manner starting from 3,4-dimethoxy aniline .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, 1 yielded an improved FRET performance in combination with the Ru (II) bathophenanthroline complex as acceptor due to a larger R 0 . 32 In addition to that, 1 was accessible in just five synthetic steps in a straightforward manner starting from 3,4-dimethoxy aniline. 32 In order to demonstrate the efficient incorporation of the three chromophore-modified building blocks 1À3, we have synthesized peptides 4À8 (Figure 4) using standard Fmoc-building blocks for the natural amino acids.…”
Section: ' Materials and Methodsmentioning
confidence: 99%